Key Technologies and Standards of Fire Prevention and Control System for Rail Transit Vehicles - Guangtai CHEN; Zheng LI; Mengyu LU; Haoqing MIAO; Hang YU; Yue ZHANG; Zheng JIANG (机车电传动)
The current development status of rail transit vehicle fire prevention and control system technology at home and abroad were introduced, and rail transit vehicle fire prevention and control system technology related standards were summarized. The R & D requirements of fire prevention and control system were analyzed, and the key technologies of rail transit vehicle fire prevention and control system were put forward, which provided some ideas for the R & D of fire prevention and control system for rail vehicles in China.